2006
DOI: 10.1038/sj.ijir.3901521
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and erectile dysfunction: meta-analysis of population-based studies

Abstract: We searched for population-based cross-sectional studies, cohort studies and randomized controlled trials (RCTs) on erectile dysfunction (ED) through Medline, PubMed, PsychInfo and scanned though reference lists. Studies that did not include adjusted odds ratios (OR) of physical activity were excluded. Seven cross-sectional studies were suitable for meta-analysis, and the results from one cross-section study, two cohort studies and one RCT were summarized. Pooling the ORs using random effects models, we derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 19 publications
5
59
0
Order By: Relevance
“…The adjusted reduction of the risk of having ED was 58% for high activity and 37% for moderate activity, as compared with men with low physical activity. 32 In the Look AHEAD (Action for Health in Diabetes), 24 cardiorespiratory fitness was found to be protective of ED among the 373 diabetic men aged 45-75 years. In particular, fitness was measured by a symptom-limited graded exercise treadmill test to voluntary exhaustion; after adjustment for age and other covariates, men with greater fitness had a 39% lower risk of ED.…”
Section: Discussionmentioning
confidence: 99%
“…The adjusted reduction of the risk of having ED was 58% for high activity and 37% for moderate activity, as compared with men with low physical activity. 32 In the Look AHEAD (Action for Health in Diabetes), 24 cardiorespiratory fitness was found to be protective of ED among the 373 diabetic men aged 45-75 years. In particular, fitness was measured by a symptom-limited graded exercise treadmill test to voluntary exhaustion; after adjustment for age and other covariates, men with greater fitness had a 39% lower risk of ED.…”
Section: Discussionmentioning
confidence: 99%
“…The adjusted reduction of the risk of having ED was 58% for high activity and 37% for moderate activity, as compared with men with low physical activity. 69 We hypothesized that lifestyle changes aimed at reducing body weight and increasing physical activity would induce amelioration of erectile and endothelial functions in obese men. We conducted a randomized controlled trial involving 110 obese men with ED.…”
Section: Lifestyle and Sexual Functionmentioning
confidence: 99%
“…Bacon et al 20,21 showed that the level of physical activity was associated with erectile dysfunction, where men with higher physical activity are less likely to suffer from erectile dysfunction. A meta-analysis performed by Cheng et al 22 showed that moderate and intense physical activities are associated with lower risk for erectile dysfunction (OD ¼ 1 for low physical activity level, OD ¼ 0.63 for moderate level and OD ¼ 0.42 for high level). Likewise, lack of physical activity was associated with higher rates of erectile dysfunction in a Thai study.…”
Section: Discussionmentioning
confidence: 99%